2022
DOI: 10.3390/ma15238418
|View full text |Cite
|
Sign up to set email alerts
|

Tailoring of Dissimilar Friction Stir Lap Welding of Aluminum and Titanium

Abstract: An approach was proposed to optimize dissimilar friction stir lap welding of aluminum and titanium alloys. The basic concept of the new technique included (i) the plunging of the welding tool solely into the aluminum part (i.e., no direct contact with the titanium side) and (ii) the welding at a relatively high-heat input condition. It was shown that sound welds could be readily produced using an ordinary cost-effective tool, with no tool abrasion and no dispersion of harmful titanium fragments within the alum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(15 citation statements)
references
References 37 publications
0
0
0
Order By: Relevance
“…Per analogy with the previous work [21], the welding tool was manufactured from tool steel and consisted of a concave-shaped shoulder of 12.5 mm in diameter and an M5-threaded probe of 1.9 mm in length. FSW was conducted under the plunge-depth control mode, while the distance between the probe tip and the interlayer material was maintained to be as small as ≈50 μm.…”
Section: Methodsmentioning
confidence: 99%
“…Per analogy with the previous work [21], the welding tool was manufactured from tool steel and consisted of a concave-shaped shoulder of 12.5 mm in diameter and an M5-threaded probe of 1.9 mm in length. FSW was conducted under the plunge-depth control mode, while the distance between the probe tip and the interlayer material was maintained to be as small as ≈50 μm.…”
Section: Methodsmentioning
confidence: 99%
“…It assumed the lap-welding configuration of a dissimilar joint and was based on the idea of plunging the FSW tool solely into the aluminum part while keeping it as close as possible to the dissimilar interface. It was shown that this technique resulted in an extremely narrow (~0.1 µm) intermetallic layer and avoided both the formation of titanium fragments and tool wear [29]. As a result, the produced joints exhibited excellent mechanical performance [29].…”
Section: Introductionmentioning
confidence: 99%
“…It was shown that this technique resulted in an extremely narrow (~0.1 µm) intermetallic layer and avoided both the formation of titanium fragments and tool wear [29]. As a result, the produced joints exhibited excellent mechanical performance [29].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Strong interactions between precipitates and dislocations are the common strengthening route for Al alloys. However, the local stress concentration will be induced along with the strengthening [1][2][3]. Under this context, one confused question has come out: what is the balance between continuous strengthening and accumulated damage?…”
mentioning
confidence: 99%